Moral Dilemmas and Worst-Case Scenarios: Using Post-Apocalyptic Fiction to Teach Criminal Justice Ethics. Issue 3 (3rd July 2019) - Mackey, David A.; Levan, Kristine
Abstract: Criminal justice courses offer ideal opportunities to present students with contemporary issues that ideally will encourage reflection on moral dilemmas. In a criminal justice ethics course, students encounter complex aspects of the topic, such as the application of theories of ethical reasoning beyond merely an understanding of the malfeasance, nonfeasance, and misfeasance of practitioners in the system. A supplemental book, whether fiction or nonfiction, assigned in addition to a criminal justice ethics textbook may facilitate deeper understanding of theories of ethics. The ideal supplemental reading should reflect the range of ethical theories detailed in the main text. In the present article, the authors discuss and evaluate the use of post-apocalyptic fiction, a popular contemporary genre, as supplemental reading in criminal justice ethics courses. A sample criminal justice ethics course writing assignment, a grading rubric, and a discussion of the multiple assessment measures are provided. Assessment results suggest that the supplemental reading helps students meet the course learning objective, which requires students to identify and apply theoretical models of ethics to specific ethical and moral situations.